Unique approaches in developing novel nano-composites: Evaluating their mechanical and tribological characteristics - Sri Ram Vikas Kodamasimham; Rahul; Venkata Ramana Vuppala Sesha Narasimha; Morampudi Priyadarsini; Bhavani Koona; Madhusudhan Reddy Gankidi (Journal of the Mechanical Behavior of Materials)
In this study, aluminium surface nano-composites were made by adding secondary phase reinforcement powder particles to the surface and sub-surface layers using friction stir processing (FSP). The study examines the development and tribological properties of aluminium-based surface nano-composites. Initial processing of tungsten (W) and aluminium-oxide (Al2O3) elemental powders involved high-energy ball milling to minimize particle size. After 25 h of milling, the tungsten grain size was 5 nm, while aluminium-oxide was 11 nm after 32 h. FSP was used to integrate these nanostructured reinforcement particles into the aluminium matrix. Hardness and wear tests were performed on these composites. From base to processed, composite hardness increased. More tool passes improved hardness and wear. The friction stir processed (FSPed) second-pass aluminium–tungsten specimen has 96 times greater wear resistance than the base material. The FSPed second-pass specimen of aluminium–tungsten surface composite, which had maximum wear resistance, was depth-sensing nanoindented at various peak loads and loading rates. Nano-hardness was 1.56 ± 0.33 to 1.26 ± 0.15 GPa (420 ± 3 MPa for base material). Elastic modulus readings were 93 ± 1 to 72 ± 1 GPa (70 ± 1 for base material).